Pemanfaatan Digitalisasi Kegiatan Pemasaran Dan Branding Pada UMKM Alesya Food Melalui Mitra Go-Food - RA. Bulan Anugrah Prastyaningrum; Maharani Ikaningtyas (PT. ALHAFI BERKAH INDONESIA, 2023)
Most Indonesian people and even the world community have adopted information technology in all forms of life. This is because information technology makes it easy to present information quickly. One sector that has been supporting the Indonesian economy and regional economic strength is the presence of micro, small and medium enterprises (MSMEs). When the world and Indonesian economies were in a recession, MSME actors did not have too much of a negative impact on the economic recession, in fact most MSME actors were still able to develop in supporting the progress of the national economy. These MSMEs certainly have various obstacles in the process of developing and selling their products. One of the SMEs where the KKNT-MBKM student service is in the City of Surabaya has problems in marketing factors and also product branding. Therefore, the purpose of this service activity is to plan marketing strategies for these UMKM’s to launch their business activities. The method used is qualitative with the type of data collection through observation, interviews and documentation of activities for UMKM person. The results of this service activity for UMKM products have developed and the marketing aspects are going well.